Efficacy of hydroxychloroquine as a potential antidiabetic drug - Kumar D., Mithun; Kamath, Laxminarayana; S., Narayana Reddy (International Journal of Basic & Clinical Pharmacology, 2017)
Background: India is the world’s diabetic capital. Oral antidiabetic therapy is still incomplete. Prior studies have shown that hydroxychloroquine (HCQ), a commonly used antimalarial, anti-rheumatic drug reduces the risk of developing diabetes mellitus. It probably acts by decreasing insulin metabolism- a novel mechanism of action. Methods: A systematic search was done in MEDLINE database with key words ‘Type 2 Diabetes Mellitus’, ‘Hydroxychloroquine’. Articles assessing the antidiabetic efficacy of hydroxychloroquine were reviewed and their results summarized. Results: With extensive literature search, we found out three RCTs and four Cohort studies assessing the efficacy of HCQ on glycaemic markers in patients with type 2 diabetes mellitus. Two randomized controlled trials done by Gerstein H C et al, Pareek A et al, comparing hydroxychloroquine with established antidiabetic drugs showed that there is significant reduction in glycaemic parameters with comparable similarity in both the groups (HbA1c: -0.91%±0.4%). Solomon et al in their study on patients with RA concluded that HCQ improved insulin sensitivity. Two cohort studies by Chen Y M et al and Wasko MCM et al respectively showed reduced incidence of diabetes mellitus in Systemic lupus erythematosus (Hazard ratio=0.26) and rheumatologic disease (relative risk=0.23) patients who received hydroxychloroquine. In a cohort study by Rekedal LR et al, HCQ reduced HbA1c by 0.66% compared to baseline in patients with RA. These studies also showed that hydroxychloroquine has favourable effect on lipid profile and good tolerability Conclusions: Hydroxychloroquine has a potential to enter antidiabetic armamentarium due to its efficacy and low toxicity profile. More studies are required to confirm this.